Enzymatic Conversion of Glycerol to Glyceric Acid with Immobilised Laccase in Na-Alginate Matrix - Chi, Shein Hong; Chin, S. Y.; Cheng, C. K.; Mohd Sabri, Mahmud; Chua, Gek Kee (Elsevier Ltd, 2015)
In this study, enzymatic oxidation of glycerol was performed for the production of glyceric acid. The effectiveness of immobilised laccase in Na-Alginate matrix was also verified. Glycerol was incubated at 25oC with 30 mM of 2,2,6,6-tetramethylpiperidine-N-oxyl (TEMPO), which acted as a mediator, in the presence of immobilized laccase from Trametes versicolor. Glyceric acid was quantified using HPLC, while the activity of enzyme was measured using ABTS assay. The yield of laccase activity was 90%. On the other hand, glyceric acid obtained was around 7 wt% from the total product at 24 h. In conclusion, enzymatic oxidation is able to produce comparable amount of glyceric acid through a more environmental friendly method.